The young HD 73583 (TOI-560) planetary system: two 10-M⊕ mini-Neptunes transiting a 500-Myr-old, bright, and active K dwarf. Issue 2 (15th March 2022) - Barragán, O; Armstrong, D J; Gandolfi, D; Carleo, I; Vidotto, A A; Villarreal D'Angelo, C; Oklopčić, A; Isaacson, H; Oddo, D; Collins, K; Fridlund, M; Sousa, S G; et al.
ABSTRACT: We present the discovery and characterization of two transiting planets observed by TESS in the light curves of the young and bright ( V = 9.67) star HD73583 (TOI-560). We perform an intensive spectroscopic and photometric space- and ground-based follow-up in order to confirm and characterize the system. We found that HD73583 is a young (∼500 Myr) active star with a rotational period of 12.08 ± 0.11 d, and a mass and radius of 0.73 ± 0.02 M⊙ and 0.65 ± 0.02 R⊙, respectively. HD 73583 b ( Pb = 6.3980420 _ - 0.0000062 ^ + 0.0000067 d) has a mass and radius of 10.2 _ - 3.1 ^ + 3.4 M ⊕ and 2.79 ± 0.10 R ⊕, respectively, which gives a density of 2.58 _ - 0.81 ^ + 0.95 g cm^-3 . HD 73583 c ( Pc = 18.87974 _ - 0.00074 ^ + 0.00086 d) has a mass and radius of 9.7 _ - 1.7 ^ + 1.8 M ⊕ and 2.39 _ - 0.09 ^ + 0.10 R ⊕, respectively, which translates to a density of 3.88 _ - 0.80 ^ + 0.91 g cm^-3 . Both planets are consistent with worlds made of a solid core surrounded by a volatile envelope. Because of their youth and host star brightness, they both are excellent candidates to perform transmission spectroscopy studies. We expect ongoing atmospheric mass-loss for both planets caused by stellar irradiation. We estimate that the detection of evaporating signatures on H and He would be challenging, but doable with present and future instruments.